Chronotypes and circadian timing in migraine. (April 2018) - van Oosterhout, WPJ; van Someren, EJW; Schoonman, GG; Louter, MA; Lammers, GJ; Ferrari, MD; Terwindt, GM
Background: It has been suggested that migraine attacks strike according to circadian patterns and that this might be related to individual chronotype. Here we evaluated and correlated individual chronotypes, stability of the circadian rhythm, and circadian attack timing in a large and well-characterised migraine population. Methods: In 2875 migraine patients and 200 non-headache controls we assessed differences in: (i) distribution of chronotypes (Münich Chronotype Questionnaire); (ii) the circadian rhythm's amplitude and stability (Circadian Type Inventory); and (iii) circadian timing of migraine attacks. Data were analysed using multinomial and linear regression models adjusted for age, gender, sleep quality and depression. Results: Migraineurs more often showed an early chronotype compared with controls (48.9% versus 38.6%; adjusted odds ratio [OR] = 2.42; 95% confidence interval [CI] = 1.58–3.69; p < 0.001); as well as a late chronotypes (37.7% versus 38.1%; adjusted OR = 1.69; 95% CI = 1.10–2.61; p = 0.016). Migraineurs, particularly those with high attack frequency, were more tired after changes in circadian rhythm (i.e. more languid; p < 0.001) and coped less well with being active at unusual hours (i.e. more rigid; p < 0.001) than controls. Of 2389 migraineurs, 961 (40.2%) reported early morning attack onset. Conclusion: Migraine patients are less prone to be of a normal chronotype than controls. They are more languid and more rigid when changes in circadian rhythm occur. Most migraine attacks begin in the early morning. These data suggest that chronobiological mechanisms play a role in migraine pathophysiology.